Seasonal variability and fluxes of nitrate in the surface waters over the Arctic shelf slope. Issue 9 (7th May 2015) - Randelhoff, Achim; Sundfjord, Arild; Reigstad, Marit
Abstract Understanding the present state and possible future scenarios of Arctic Ocean primary productivity has been hampered by the scarcity of year‐round nutrient measurements. Here the first yearlong moored time series of near‐surface nitrate concentrations in the Eastern Arctic, together with hydrography, currents, and chlorophyll a fluorescence, is reported from the shelf slope northeast of Svalbard. Variability was dominated by the inflow of Atlantic Water (AW). Nitrate was near depleted during July–September and reached a maximum concentration of 10 μM in March. Vertical nitrate gradients were eroded by mid‐December, demonstrating the importance of the AW in breaking down upper ocean stratification during fall. Upward nitrate fluxes through the nitracline in the AW inflow region during fall were 2.5 ± 0.5 mmol m−2 d−1. The spring bloom triggered extensive nitrate drawdown from June, from which an annual new production of 31 g C m−2 was estimated.